Monitoring and Evalution of Chickpea Pod-Borer Helicoverpa Armigera (Hubner) (Lepidoptera: Noctuidae) by Using Pheromone Traps - Hossain, M Altab (Bangladesh Journal of Scientific and Industrial Research, 2008)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if !mso]> <![endif]–> <!–[if gte mso 10]> <![endif]–> Monitoring of chickpea pod-borer, Helicoverpa armigera (Hb.) and its acvities throughtout the year was studied by installing pheromone traps at Pulses Research Center, Ishurdi, Pabna during January 2004 to December 2006. Pod-borer moth catching in pheromone traps was started between 3rd weeks of January to 2nd weeks of February depending on the climatic conditions of the year. Catching of moths was increased gradually and reached its pesk in the month of April then gradually decreased and diminished to zero in the last week of July and ultimately remained zero upto December. Integrated Pest Management Programme against chickpea podborer should be initiated from mid-January to manage this pest population very effectively. Key words : Monitoring, Chickpea, Pest Management, Pod-borer and Catching of moths. DOI = 10.3329/bjsir.v43i3.1159 Bangladesh J. Sci. Ind. Res. 43(3), 419-426, 2008